Religiusitas dengan authentic happiness pada Pelajar - Rasyid, Abdullah; Pandya, Muhammad Fikran (UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to determine the relationship between religiosity and authentic happiness in MAN 2 Pasuruan students. This research uses quantitative methods by looking at the correlation between two variables. The scales used in this research are the religiosity scale (validity: 14 items, coefficient value > 0.300, reliability 0.903) and the authentic happiness scale (validity: 1 item, coefficient value > 0.300, reliability 0.961). The number of respondents was 275 MAN 2 Pasuruan students taken from classes X, XI, and XII randomly via a questionnaire. The data analysis technique in this study used product moment analysis with a correlation coefficient of 0.135 and a significance level of 0.025